2022
DOI: 10.1039/d2ta05109e
|View full text |Cite
|
Sign up to set email alerts
|

Multiple strategies of porous tetrametallene for efficient ethanol electrooxidation

Abstract: The first synthesized porous Pd59W8Rh19Bi14 metallene combines OH adsorption effects, electronic effects and C–C bond cleavage site strategies to improve EOR performance. The metallene stable structure further accelerates the mass transfer rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…In recent years, noble metal-based metallenes have emerged as a highly efficient class of two-dimensional electrocatalysts owing to their considerably high atomic utilization, specific surface area, and exposure to active sites [38][39][40][41][42][43][44][45][46][47][48]. The optimized contact of the electrocatalysts with supports is also guaranteed through the construction of such twodimensional materials.…”
Section: Dimensional Engineering Of Pt-based Alloys For Mormentioning
confidence: 99%
“…In recent years, noble metal-based metallenes have emerged as a highly efficient class of two-dimensional electrocatalysts owing to their considerably high atomic utilization, specific surface area, and exposure to active sites [38][39][40][41][42][43][44][45][46][47][48]. The optimized contact of the electrocatalysts with supports is also guaranteed through the construction of such twodimensional materials.…”
Section: Dimensional Engineering Of Pt-based Alloys For Mormentioning
confidence: 99%
“…Previous in situ Raman studies have demonstrated that the reaction pathways for various PGM catalysts can significantly differ [33–35] . Many commercial Pd/C or Pt/C catalysts exhibit relatively low C1 selectivity [36] .…”
Section: In Situ Raman Investigations Of Reaction Pathways For Pgm‐ba...mentioning
confidence: 99%
“…Previous in situ Raman studies have demonstrated that the reaction pathways for various PGM catalysts can significantly differ. [33][34][35] Many commercial Pd/C or Pt/C catalysts exhibit relatively low C1 selectivity. [36] Nonetheless, it is possible to judiciously design a PGM-based catalyst to shift its performance toward the more favorable C1À 12e À pathway.…”
Section: In Situ Raman Investigations Of Reaction Pathways For Pgm-ba...mentioning
confidence: 99%
“…[14,15] However, there are few reports regarding NbN-based catalysts towards alkaline EOR, especially on the ability to break the C-C bonds. In addition, doping the oxygen-ophilic metals is also an effective strategy to improve the anti-poisoning ability of electrocatalysts for EOR, which can enhance the adsorption of OH and further promote the oxidative removal of CO. [16] In our previous work, we reported PdSn-TaN/C for alkaline MOR, which can provide more efficient surface interface active sites, thereby improving MOR catalytic performance. [7] Nevertheless, EOR exhibits a more complex and slower oxidation process than MOR, and the reaction process involves the decomposition and splitting of C-C. [17] Combined with the previous research, TMNs are expected to break the C-C bonds of ethanol in alkaline media through interfacial sites, and the oxidation rate of CO-like intermediates is increased by doping with the oxyphilic metals.…”
Section: Introductionmentioning
confidence: 99%